Zoledronate Attenuates Accumulation of DNA Damage in Mesenchymal Stem Cells and Protects Their Function. (22nd December 2015) - Misra, Juhi; Mohanty, Sindhu T.; Madan, Sanjeev; Fernandes, James A.; Hal Ebetino, F.; Russell, R. Graham G.; Bellantuono, Ilaria
Abstract: Mesenchymal stem cells (MSCs) undergo a decline in function following ex vivo expansion and exposure to irradiation. This has been associated with accumulation of DNA damage and has important implications for tissue engineering approaches or in patients receiving radiotherapy. Therefore, interventions, which limit accumulation of DNA damage in MSC, are of clinical significance. We were intrigued by findings showing that zoledronate (ZOL), an anti-resorptive nitrogen containing bisphosphonate, significantly extended survival in patients affected by osteoporosis. The effect was too large to be simply due to the prevention of fractures. Moreover, in combination with statins, it extended the lifespan in a mouse model of Hutchinson Gilford Progeria Syndrome. Therefore, we asked whether ZOL was able to extend the lifespan of human MSC and whether this was due to reduced accumulation of DNA damage, one of the important mechanisms of aging. Here, we show that this was the case both following expansion and irradiation, preserving their ability to proliferate and differentiate in vitro. In addition, administration of ZOL before irradiation protected the survival of mesenchymal progenitors in mice. Through mechanistic studies, we were able to show that inhibition of mTOR signaling, a pathway involved in longevity and cancer, was responsible for these effects. Our data open up new opportunities to protect MSC from the side effects of radiotherapy in cancer patients and during ex vivo expansion for regenerative medicine approaches. Given that ZOL is already in clinical use with a good safety profile, these opportunities can be readily translated for patient benefit.